2013
DOI: 10.1016/j.cej.2013.04.096
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced total nitrogen removal performance in a modified Orbal oxidation ditch system with internal nitrate recycle

Abstract: h i g h l i g h t sAn Orbal oxidation ditch with nitrate recycle for enhanced TN removal was developed. The optimal DO for SND was 0.15-0.25 mg/L. The highest TN removal was achieved at internal recycle ratio of 9.4. Nitrogen mass balances confirmed SND coupled with pre-denitrification. Nitrogen removal was closely related to bacterial community composition. a r t i c l e i n f o b s t r a c tA pilot-scale modified Orbal oxidation ditch with internal recycle of the nitrified liquor was developed to significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Research has shown that simultaneous nitrification and denitrification (SND) will be stimulated in an Oxidation Ditch, which benefits high TN removal (Zhou et al 2013). In this research, similar results were observed.…”
Section: Resultsmentioning
confidence: 99%
“…Research has shown that simultaneous nitrification and denitrification (SND) will be stimulated in an Oxidation Ditch, which benefits high TN removal (Zhou et al 2013). In this research, similar results were observed.…”
Section: Resultsmentioning
confidence: 99%
“…It was concluded that such a relatively low DO concentration was sufficient for nitrification, meanwhile, without inhibitory effects on denitrification at the presence of large macroscopical aerated-anoxic environment of the outer channel [17,27,28]. According to above results, it was likely that obvious SND was efficiently accomplished at a moderately low level of oxygen supply [13,16] in the outer channel which provided continuous alternation between anoxic and micro-aerobic conditions both in space and time to maintain equally high dynamic balances between nitrification and denitrification rates. force depended on the number of disc aerators under identical operational parameters.…”
Section: Nitrogen Mass Balancesmentioning
confidence: 87%
“…Until now, SND phenomenons have already been successfully observed in lab- [11], pilot- [11][12][13][14] and even full-scale OD systems [15][16][17]. There were some principal explanations or presumptions for nitrogen removal via SND in oxidation ditches: (1) repeatedly swift alternation is between aerobic (after aerators) and anoxic zones (before aerators) of the mixed liquor in the same aerated channel based on inhomogeneous oxygen distribution [18]; (2) low-oxygen nitrification occurs at low sludge loading rate or long HRT and SRT [14,16,17], despite its nitrification rate is generally maximum value at DO of above 2.0 mg L À1 ; (3) anoxic zones are developed inside the activated-sludge flocs under aerobic conditions [14,19]; (4) novel microbes such as aerobic denitrifiers and nitrifiers adapted to low-oxygen conditions [16,20] are capable of performing SND.…”
Section: Introductionmentioning
confidence: 99%
“…Of particular interest are the experiences described by US-EPA, which shows how to upgrade plants in order to achieve fluctuation control [1], and in which more cautious design criteria are recommended for wastewater treatment plants (WWTPs) serving small communities [2]. With specific reference to the effects on biological denitrification, the scientific literature provides abundant information on nitrogen removal [3][4][5][6][7][8][9][10][11], but rarely refers to small WWTPs. The effects of raw sewage C/N ratio variations in small community WWTPs have been highlighted in the technical literature [12][13][14], which also show the possible negative side effects of dissolved oxygen accumulation in the denitrification stage.…”
mentioning
confidence: 99%